Shipwreck - Washburn, Anne (Oberon modern plays., 2018)
'From across the room I saw the President, torchlight playing across his visage.And the violins began, and the low rumble of the timpani.I screamed. I ran.' An old farmhouse upstate. Snow is falling. Mountains are falling. Something is breaking apart. You are formally invited to dinner with the 45th President of the United States. Shipwreck received its UK premiere at the Almeida Theatre from 11 February ' 30 March 2019, in a production directed by Rupert Goold.